Immunotherapy in elderly head and neck cancer patients: a systematic review and meta-analysis - Salvestrini, Viola; Caini, Saverio; Scricciolo, Melissa; Saerens, Michael; Bollen, Heleen; Bonomo, Pierluigi; Caparrotti, Francesca; Lorini, Luigi; Oliva, Marc; Urbanowicz-Nijaki, Maria; Szturz, Petr (Frontiers in Oncology, 2024)
Introduction Over the past years, there has been a growing interest in the role of immunotherapy in locally advanced (LA) and recurrent and metastatic head and neck squamous cell carcinoma (R/M HNSCC). High-quality data from prospective trials are lacking for the elderly subpopulation. This systematic review and meta-analysis aims to review the efficacy and safety of immunotherapy in older patients. Methods A systematic literature search was conducted. Randomized clinical trials providing outcome data on a subgroup of elderly (>65 years old) were available for meta-analysis. Primary outcomes of interest were OS and PFS for efficacy analysis. Results Seven studies were included in the systematic review and four in the efficacy analysis. The pooled analysis of OS and PFS showed a consistent benefit (HR 0.78 and 0.91, respectively). Conclusions Immunotherapy may be an effective and well-tolerated treatment option in the elderly population, but more prospective and randomized data are needed. Systematic Review Registration PROSPERO (CRD42022333891).